When advertisements are disguised as news: the ethics problem in Indonesian mass media - Krisdinanto, Nanang (Jurnal Studi Komunikasi, 2021)
The practice of obscuring news and advertising is still a problem in the Indonesian mass media. This research aimed to unravel journalistic ethics problems, especially those related to advertorials (advertisements delivered in an editorial style). The clear separation between news and advertisements is one of the two pillars of journalistic ethics, apart from separating facts and opinions to maintain journalistic independence. The research approach used was qualitative-descriptive, with data collection techniques through interviews (to journalists), observation and document searches. The results showed that most of the printed mass media studied tended to blur the boundaries between news and advertisements through various means, such as removing or shortening advertorial information.